Does trust matter? examining the impact of socialisation, knowledge, and religiosity on employee performance in banking sector - Hasibuan, Lempang; Supriyanto, Achmad Sani; Ekowati, Vivin Maharani; Maksum, Ikhsan; Khan, Ryan Basith; Sani, Ahmad Firza Fahreza; Ahamed, Forbis (BISMA (Bisnis dan Manajemen), 2025)
Knowledge is a critical factor in improving performance and achieving competitive advantage. The purpose of this study is to determine the mediating role of trust in the relationship of socialisation, knowledge, and religiosity toward employee performance in banking sector. This research is quantitative with an explanatory approach. This study surveyed 200 employees of a sharia bank in Indonesia and collected 112 respondents return the questioner. The data analysed using Partial Least Squares Structural Equation Modelling (SEM-PLS). This study confirms that socialisation and knowledge do not affect employee performance directly. Religiosity affects employee performance. Trust mediates the effect of socialisation, knowledge, and religiosity on employee performance. The study provides new evidence on trust in Islamic banking sector related to socialisation, knowledge, religiosity and employee performance. Managers in Islamic banks should strengthen internal socialisation and knowledge-sharing programs that are grounded in religious values to foster greater trust among employees. By prioritising trust-building, managers can enhance employee commitment and overall performance, creating a more cohesive and value-driven organisational culture.